Reframing Sustainability: Visual Rhetoric Of Eco-Influencers In Instagram Reels Campaigns - Anialasalam, Ayla; Yousef, Yildirim; Agustianingrum, Indira (University of Science and Computer Technology, 2025)
Recent shifts in digital communication have transformed how sustainability is visually framed and communicated to the public. Rather than relying on traditional environmental campaigns, eco-influencers now use short-form video content on platforms like Instagram Reels to convey persuasive sustainability narratives. This study explores how visual rhetoric operates in these Reels-based campaigns to shape audience perceptions of environmental responsibility. Employing a mixed-methods approach that integrates semiotic analysis with audience reception research, this paper analyzes selected Instagram Reels produced by prominent Southeast Asian eco-influencers. The study identifies recurring patterns in visual symbolism, aesthetic presentation, and narrative framing that enhance the persuasive impact of these videos. Key semiotic elements such as symbolic color palettes, natural imagery, and expressive gestures were found to heighten emotional engagement and clarity of message. Findings from the audience survey reveal that viewers respond more positively to sustainability messages presented through authentic, aspirational storytelling rather than overtly moralistic appeals. This study is among the first to examine eco-influencers’ short-form video rhetoric within Southeast Asian cultural contexts, addressing a gap in current green marketing and visual communication literature. By focusing on the intersection of visual persuasion, influencer marketing, and short-form digital content, the research contributes a design-oriented perspective to environmental communication studies. It positions eco-influencers as visual rhetoricians who transform sustainability into an experiential, algorithm-driven form of digital storytelling.